2017
DOI: 10.35188/unu-wider/2017/392-9
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the metal ceiling: Female entrepreneurs who succeed in male-dominated sectors

Abstract: Occupational segregation significantly contributes to the earnings gender gap worldwide. We look at differences in outcomes for male and female enterprises and their sectors in Sub-Saharan Africa, a region of high female participation in entrepreneurship. Data on Uganda show that women breaking into male-dominated sectors make as much as men, and three times more than women staying in female-dominated sectors. Factors including entrepreneurial skill/abilities and credit/human capital constraints do not explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 21 publications
3
37
0
2
Order By: Relevance
“…3 A study of Ugandan entrepreneurs found that women who enter male-dominated trades, referred to as "cross-overs," were more likely to have received technical and business training, have better financial literacy skills, and learn through an internship or apprenticeship. Surprisingly, higher educational attainment or years of previous experience did not increase a women's likelihood of being a cross-over (Campos et al, 2015).…”
Section: Educational Attainment and Educational Choicementioning
confidence: 67%
See 3 more Smart Citations
“…3 A study of Ugandan entrepreneurs found that women who enter male-dominated trades, referred to as "cross-overs," were more likely to have received technical and business training, have better financial literacy skills, and learn through an internship or apprenticeship. Surprisingly, higher educational attainment or years of previous experience did not increase a women's likelihood of being a cross-over (Campos et al, 2015).…”
Section: Educational Attainment and Educational Choicementioning
confidence: 67%
“…Studying household decision making, Duflo and Udry (2004) showed that household consumption in Cote D'Ivoire varied with the identity of the owner and the source of the income. In Uganda, women entrepreneurs who worked in male-dominated trades were more likely to spend on school expenses than women in female-dominated trades (Campos et al, 2015).…”
Section: Why Gender-based Employment Segregation Mattersmentioning
confidence: 98%
See 2 more Smart Citations
“…Enabling women to shift to high value commercial crops shows promise in Africa. Access to information about potential returns for women in male-dominated fields can help female entrepreneurs cross over and shift sectors (Campos et al, 2015), provided they also get support from male mentors in the field and can withstand sexual harassment and barriers to access credit.…”
Section: Solving Market and Institutional Failuresmentioning
confidence: 99%